2011
DOI: 10.1017/s0021859611000918
|View full text |Cite
|
Sign up to set email alerts
|

Legumes intercropped with spring barley contribute to increased biomass production and carry-over effects

Abstract: Intercropping systems that include legumes can provide symbiotically fixed nitrogen (N) and potentially increase yield through improved resource use efficiency. The aims of the present study were: (a) to evaluate the effects of different legumes (species and varieties) and barley on grain yield, dry matter production and N uptake of the intercrop treatments compared with the associated cereal sole crop; (b) to assess the effects on the yields of the next grain crop and (c) to determine the accumulation of N in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 56 publications
(103 reference statements)
2
24
0
Order By: Relevance
“…Thus, Liu et al (2006) reported that NT can reduce CH 4 uptake compared to that of CT, whereas Jacinthe et al (2014) showed that the maintenance and duration of NT increased CH 4 oxidation. On the other hand, legume-cereal rotations are promoted as sustainable cropping systems, both in conservation and conventional agriculture, because the legume crop provides an additional N supply for the cereal decreasing the requirements for application of N fertilizers (Pappa et al 2012). Jensen et al (2012) found that N 2 O fluxes from legumes were not significantly different to background emissions and were also lower than comparable N-fertilized crops and pastures.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Liu et al (2006) reported that NT can reduce CH 4 uptake compared to that of CT, whereas Jacinthe et al (2014) showed that the maintenance and duration of NT increased CH 4 oxidation. On the other hand, legume-cereal rotations are promoted as sustainable cropping systems, both in conservation and conventional agriculture, because the legume crop provides an additional N supply for the cereal decreasing the requirements for application of N fertilizers (Pappa et al 2012). Jensen et al (2012) found that N 2 O fluxes from legumes were not significantly different to background emissions and were also lower than comparable N-fertilized crops and pastures.…”
Section: Introductionmentioning
confidence: 99%
“…Additional advantages of cereal/legume intercropping include (i) more efficient exploitation of the N resource, due to the complementarity of biological N 2 fixation and soil mineral N use by companion plants; (ii) reduction in leaching N losses; and (iii) a positive residual effect on the next crop (Hauggaard-Nielsen et al 2003, Szumigalski and van Acker 2006, Pappa et al 2012.…”
mentioning
confidence: 99%
“…Since the choice of cultivar is a key factor influencing interspecific competition and the amount of N available to the system (Ross et al 2004, Pappa et al 2012, the combination of four barley (two 2-row and two 6-row) and two field bean cultivars was compared.…”
mentioning
confidence: 99%
“…In order to shed some light on the mutual interaction of intercropped species, and on the advantages of intercropping, the influence of this management practice on the yield and economic returns has been recently evaluated . These studies have allowed to stress intercrop systems on their capacity to improve the efficiency of irrigation and solar radiation, while enhancing pollination, grain yield, and total protein content …”
Section: Introductionmentioning
confidence: 99%